Effects of Infliximab in a Propionic Acid-Induced Experimental Autism Rat Model - Akman, Nur; Komuroglu, Ahmet Ufuk; Cibuk, Salih; Altindag, Fikret; Yilmaz, Osman; Atessahin, Ahmet (Mdpi, 2026)
Background/Objectives: Autism spectrum disorder (ASD) is a neurodevelopmental condition increasingly associated with dysregulated neuroimmune signaling and altered neurotrophic homeostasis. Tumor necrosis factor-alpha (TNF-alpha) has been implicated in ASD pathophysiology; however, the downstream effects of TNF-alpha blockade on cytokine-neurotrophin interactions during neurodevelopment remain insufficiently characterized. In this study, we evaluated the effects of infliximab (IFX), a monoclonal anti-TNF-alpha antibody, on behavioral performance, neuroinflammatory cytokine profiles, glial activation, and brain-derived neurotrophic factor (BDNF) signaling in a propionic acid (PPA)-induced experimental ASD rat model. Methods: Experimental ASD was induced by propionic acid administration in rats. Animals were divided into control and treatment groups. Behavioral performance was assessed using the Morris Water Maze, direct social interaction, and three-chamber sociability tests. Levels of TNF-alpha, interleukin-1 beta (IL-1 beta), interleukin-6 (IL-6), and BDNF were measured in serum, hippocampal, and cerebellar tissues. Microglial and astrocytic activation were evaluated using CD11 and GFAP immunohistochemistry. Results: PPA administration resulted in pronounced impairments in learning, memory, and social behaviors, accompanied by elevated proinflammatory cytokine levels, increased BDNF expression, and marked glial activation in the hippocampus and cerebellum. Although IFX treatment significantly reduced TNF-alpha levels in central tissues, it did not improve behavioral deficits and was associated with persistently elevated IL-1 beta and IL-6 levels, sustained glial reactivity, and further alterations in BDNF levels. Conclusions: These findings suggest that TNF-alpha suppression alone does not normalize the disrupted cytokine-neurotrophin axis and may differentially modulate BDNF-related neuroplastic signaling during development. In conclusion, this study indicates that non-selective TNF-alpha blockade during neurodevelopment fails to confer behavioral benefit in experimental ASD and highlights the importance of considering cytokine-BDNF pathway interactions when designing immunomodulatory strategies for neurodevelopmental disorders.
Keywords: autism spectrum disorder; propionic acid; infliximab; neuroinflammation; glial activation; BDNF